2019
DOI: 10.1016/j.wasman.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and economic assessment of sludge thermal hydrolysis in novel wastewater treatment plant configurations

Abstract: Novel wastewater treatment plants (WWTPs) are aimed to be more energetically efficient than conventional ones. Their first step is a chemical oxygen demand (COD) preconcentration stage with different alternatives, such as rotating belt filters (RBF), chemically enhanced primary treatment (CEPT), high-rate activated sludge (HRAS), or combinations thereof, in which energy requirements are substantially reduced. The COD recovered as sludge allows a noticeable increase of biogas production in anaerobic digestion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Taken into consideration that there is no need for aeration in the CEPT process applied in the current study, energy requirement would be highly reduced by adopting such treatment strategy. This is also supported with the recent findings of Taboada-Santos et al [39], who reported that the electricity consumption for CEPT process is below 0.01 kWh/m 3 . Indeed, energy produced from primary sludge through anaerobic digestion could reduce the electricity cost and WWTP could become energy self-sufficient by generating renewable energy [18].…”
Section: Energy Gain and Circular Economy Perspectivesupporting
confidence: 91%
“…Taken into consideration that there is no need for aeration in the CEPT process applied in the current study, energy requirement would be highly reduced by adopting such treatment strategy. This is also supported with the recent findings of Taboada-Santos et al [39], who reported that the electricity consumption for CEPT process is below 0.01 kWh/m 3 . Indeed, energy produced from primary sludge through anaerobic digestion could reduce the electricity cost and WWTP could become energy self-sufficient by generating renewable energy [18].…”
Section: Energy Gain and Circular Economy Perspectivesupporting
confidence: 91%
“…From an economic point of view, it is energy and waste disposal costs that are important. The energy costs associated with achieving high temperatures are offset by savings resulting from no waste landfilling fees (Taboada-Santos et al 2019b ).…”
Section: Sludge Treatment Methodsmentioning
confidence: 99%
“…Taboada‐Santos, Lema, and Carballa (2019) assessed the sludge THP in novel WWTP schemes from an energy and economic perspective. The contribution of THP to novel WWTP economy was mainly due to the sludge disposal saving rather than the increase of energy production, and a total solid content higher than 1%–2% for thermal hydrolysis of sewage sludge was necessary to achieve the reduction in operational cost.…”
Section: Wastewater and Sludge Treatmentmentioning
confidence: 99%